Creation of Civil Engineering Competence Framework in Project CALOHEE - Alfredo Soeiro (2022)
Throughout the 2000s, higher education institutions, both in Japan and abroad, have aimed at moving toward learner-centered education and quality assurance of education based on learning outcomes. Tuning, which supports the development of disciplinary reference points and the development and promotion of methodologies for designing degree programs based on learning outcomes, is one of the representative initiatives. Since its inception in 2000, Tuning has been accepted by higher education institutions not only in Europe but also in other parts of the world including the United States, and has also had impact on higher education policy in Japan. During the 2010s, the Learning Outcomes Initiative achieved a certain level of success, and simultaneous efforts to substantiate the Initiative were being made by higher education institutions around the world. The outbreak of COVID-19 has made it difficult to continue education face-to-face, pushing higher education institutions to deliver education online. While we have witnessed positive impacts of online education such as the dramatic progress in the visualization of student learning processes, we must also admit that during this time, the Learning Outcomes Initiative stagnated, and educational practice suffered to certain extents. As most of us have successfully acquired the basic skills necessary to conduct education and research online, it is time that we look ahead to the future of higher education in coexistence with the coronavirus. What do the ideas and methodologies of learner-centered education that we have developed throughout the 2000s mean, and how do they contribute to the advancement of higher education in the context of new normal? In this symposium, we invite speakers who have played central roles in promoting learner- centered education and quality assurance of education based on learning outcomes to share their recent experiences as well as their visions of higher education in coexistence with the coronavirus. By bringing together panelists and symposium participants from around the globe that share their passion for learner-centered education and quality assurance of education based on learning outcomes, we hope to create solidarity that will support each of us in taking new bold steps towards advancing higher education in coexistence with the coronavirus. Satoko Fukahori, Principal Investigator of the Sponsoring Research Group Kayo Matsushita, Principal Investigator of the Co-organizing Research Group Keiichi Yoshimoto, Principal Investigator of the Co-organizing Research Group